MAIN ISSUES OF REFLECTING ECOTERMS IN TRANSLATION - Nigmatullina, Almira Shamsunovna (Журнал иностранных языков и лингвистики, 2023)
The methods of searching for an equivalent in translation are considered, taking into account the process of replacing the content of a linguistic sign to replace it with a new, specially created concept in the field of ecology. The use of environmental terms in translations is analyzed.